Compositional analysis of interrogative imperatives in Hungarian - Judit Kleiber; Gábor Alberti (LingBaW)
The paper investigates utterances which combine imperative and interrogative elements in Hungarian. We intend to explore the scope of the hypothesis that the pragmatico-semantic content of mixed-type sentences can be obtained compositionally. We present four types of interrogative imperative. The imperative factor is indicated by subjunctive morphology on the verb. The interrogative character is represented by (1) rise-fall intonation which marks polar questions, (2) the discourse marker ugye expressing bias, (3) the particle vajon expressing self-reflection or hesitation, and (4) wavy intonation which indicates surprise. We claim that such sentences are primarily questions with their main function being ‘request for instruction’. For the analysis, we take a formal pragmatico-semantic point of view. Our goal is to demonstrate how these sentences can be analyzed compositionally within a belief–desire–intention frame. We apply the formal dynamic discourse- and mind-representation theory ReALIS. We have found that the pragmatico-semantic content (intensional profile) of each type can be constructed via using two formal operations: concatenation and pragmasemantic blending. The composition produces the required output, namely that the interrogation / bias / speculation / surprise which pertains to an eventuality in the case of a simple question, pertains to the “commanding” of this eventuality in the case of interrogative imperatives.